A case of hemorrhagic shock occurred during dienogest therapy for uterine adenomyosis. Issue 12 (8th October 2020) - Takamura, Masashi; Koga, Kaori; Harada, Miyuki; Hirota, Yasushi; Fujii, Tomoyuki; Osuga, Yutaka
Abstract: We present a case of hemorrhagic shock occurred during dienogest therapy for uterine adenomyosis which necessitated an emergency hysterectomy. The patient was a 45‐year‐old woman with adenomyosis. Magnetic resonance imaging showed type I adenomyosis measuring 10 cm. She had a history of intimal thrombectomy of pulmonary embolism and had been receiving warfarin and aspirin until the onset of the hemorrhagic shock. Following 6‐month of gonadotropin‐releasing hormone analogue, dienogest was commenced. Nine months after switching to dienogest, the patient experienced a persistent abnormal uterine bleeding for 2 weeks, eventually causing a massive bleeding and was transferred to our emergency room. A diagnosis of hemorrhagic shock with a severe anemia (hemoglobin 3.6 g/dL) was made. Despite blood transfusion and warfarin antagonization, continuous bleeding ≥150 g/h was not controlled. Emergent hysterectomy was opted and enabled hemostasis. Although the number of patients with adenomyosis who can avoid surgery by dienogest is increasing, care must be taken during dienogest therapy, especially in patients with anticoagulants and after gonadotropin‐releasing hormone analogue treatment. To prevent such a critical event, careful management including patient education should be carried out.